2017
DOI: 10.1186/s12889-017-4787-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between parent attitudes and receipt of human papillomavirus vaccine in adolescents

Abstract: BackgroundHuman papillomavirus (HPV) vaccine coverage rates remain low. This is believed to reflect parental hesitancy, but few studies have examined how changes in parents’ attitudes impact HPV vaccine uptake. This study examined the association between changes in parents’ vaccine attitudes and HPV vaccine receipt in their adolescent children.MethodsA baseline and 1-year follow-up survey of HPV vaccine attitudes was administered to parents of 11–17 year olds who had not completed the HPV vaccine series. Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
5
27
2
Order By: Relevance
“…Contrary to our findings, other studies in high income countries have found that HPV knowledge and fear of adverse events could be important barriers to HPV vaccine uptake [32,[39][40][41]. Ogilvie et al found that in British Columbia, Canada, the main reason for having girls vaccinated was the vaccine's effectiveness, while the main reasons for not having girls receive the vaccine were concerns about its safety, preference to wait until girls were older, and not enough information to make informed decisions [32].…”
Section: Plos Onecontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, other studies in high income countries have found that HPV knowledge and fear of adverse events could be important barriers to HPV vaccine uptake [32,[39][40][41]. Ogilvie et al found that in British Columbia, Canada, the main reason for having girls vaccinated was the vaccine's effectiveness, while the main reasons for not having girls receive the vaccine were concerns about its safety, preference to wait until girls were older, and not enough information to make informed decisions [32].…”
Section: Plos Onecontrasting
confidence: 99%
“…This is supported by other studies which have found similar results. For example, VanWormer PLOS ONE et al showed that neither physicians' nor nurses' recommendations to get the HPV vaccine in the previous year were associated with the actual receipt of the next HPV vaccine dose [40]. It is worth noting that in our study, only 72% of caregivers reported to have been advised by physicians to vaccinate their daughters.…”
Section: Plos Onecontrasting
confidence: 67%
See 1 more Smart Citation
“…38 The present study was unique in evaluating PAPM stages for both parents of girls and boys. The literature has primarily focused on parents of girls, 35,[37][38][39][40][41][42][43][44] with none using the PAPM.…”
Section: Discussionmentioning
confidence: 99%
“…For the 10 Marshfield Clinic sites, additional characteristics were available from EMR extraction for all patients who met the initial eligibility criteria of age, BMI, rural residence, clinic visit within 18 months, and were medically-homed to the Marshfield Clinic Health System with reasonably complete capture of all medical care, per standard quality reporting definitions used by the Marshfield Clinic Institute for Quality, Innovation and Patient Safety [26]. Additional extracted variables included comorbid conditions, smoking status, number of ambulatory visits, and in-patient days over the past 3 years.…”
Section: Characteristics Of Participants Versus Non-participantsmentioning
confidence: 99%